Х +4/15 = 2/3+ 2/5( 4/5 - х ) +13/20 = 25/30 у - 5/20 = 5/8 - 3/10 2/3 - (7/9 - а) =1/3

Х +4/15 = 2/3+ 2/5 ( 4/5 - х ) +13/20 = 25/30  у - 5/20 = 5/8 - 3/10  2/3 - (7/9 - а) =1/3
Гость
Ответ(ы) на вопрос:
Гость
х=2/3+2/5-4/15 х=12/15+4/15=16/15 (4/5-х)=25/30-13/20=500-390/600=110/600=11/60 х=4/5-11/60=48-11/60=37/60 у=5/8-3/10+5/20 у=23/40 (7/9-а)=2/3-1/3 (7/9-а)=1/3 а=7/9-1/3 а=7-3/9=4/9
Гость
х + 4/15 = 2/3 + 2/5 х + 4/15 = 10/15 + 6/15 х + 4/15 = 16/15 х = 16/15 - 4/15 х = 12/15 = 4/5          4/5 + 4/15 = 2/3 + 2/5 12/15 + 4/15 = 10/15 + 6/15 16/15 = 16/15 Ответ : х = 4/5 (4/5 - х) + 13/20 = 25/30 4/5 - х = 25/30 - 13/20 4/5 - х = 50/60 - 39/60 4/5 - х = 11/60 х = 4/5 - 11/60 х = 48/60 - 11/60 х = 37/60            (4/5 - 37/60) + 13/20 = 25/30 (48/60 - 37/60) + 13/20 = 25/30 11/60 + 13/20 = 25/30 11/60 + 39/20 = 25/30 50/60 = 25/30 25/30 = 25/30 5/6 = 5/6 Ответ: х = 37/60 у - 5/20 = 5/8 - 3/10 у - 5/20 = 25/40 - 12/40 у - 5/20 = 13/40 у = 13/40 + 5/20 у = 13/40 + 10/40 у = 23/40             23/40 - 5/20 = 5/8 - 3/10 23/40 - 10/40 = 25/40 - 12/40 13/40 = 13/40 Ответ: у = 23/40 2/3 - (7/9 - а) = 1/3 7/9 - а = 2/3 - 1/3 7/9 - а = 1/3 а = 7/9 - 1/3 а = 7/9 - 3/9 а = 4/9            2/3 - (7/9 - 4/9) = 1/3 2/3 - 3/9 = 1/3 6/9 - 3/9 = 1/3 3/9 - 1/3 1/3 = 1/3 Ответ: а = 4/9
Не нашли ответ?
Ответить на вопрос
Похожие вопросы